Determinan Fertilitas Pada Suku Anak Dalam (SAD) Provinsi Jambi - munandar, arif (Brida Provinsi Jambi, 2024)
Fertility is the ability of a woman to give birth to a child alive during her reproductive years, the baby born shows signs of life, including heartbeat, moving, breathing, crying and others. This study was conducted to identify Factors affecting Fertility in Orang Rimba in Jambi Province. The research design used was an Observational Analysis Study, with research locations in Jelutih Village, Batin XXIV District, Batanghari Regency and in Bukit Suban Village, Air Hitam District, Sarolangun Regency, Jambi Province. Sample determination using the Proportional Simple Random Sampling method, with data analysis using the Structural Equation Modeling (SEM) equation model with the SmartPLS application. The results of the analysis showed that demographic, conception and environmental variables (programs) proved to have a real and significant effect with fertility variables (p-value< 0.05). Specifically, there is a structural relationship (p-value 0.062) between Intercourse-> Conception-> Fertility. Increasing the intercourse variables (first HUS age, first marriage age) will reduce conception variables (use of birth control devices, the length of vulnerable HUS time after childbirth and increasing the first age of childbirth) thus having an impact on decreasing fertility rates in SAD in Jambi Province. Keywords: fertility, norm, environment, intercourse, conception